(untitled) (ENTHYMEMA, 2019)
This essay aims to investigate the construction of the autobiographical self, in the light of contemporary narratives theories. The aim of this essay is to analyse not only the narrative styles, the cultural traditions and the social context from which the narrations take place, but also the possible distance between the construction of the Western self and of the Eastern one. The analysis will try to understand if the contemporary transnational flows and the deterritorialization could be taken into account by the cognitive narratology. In particular, the attention will be focused on the chance of this theoretical approach to keep in mind these changes and the fluidity of contemporary storytelling, which inevitably lead to the existence of flexible identity structures.